Intersectional Audiard: Masculinity and Race in Dheepan and The Sisters Brothers - Laura Mason (Mise au Point)
This article follows the lead of Richard Dyer and Devon Carbado in naming whiteness as a racial identity and uses intersectional analysis to explore Jacques Audiard’s depiction of race and gender in Dheepan and The Sisters Brothers. Both movies depart from the gender norms of earlier Audiard films by doing away with female saviors, so making male protagonists responsible for controlling their own violence. Both films also reflect Audiard’s determination to foreground Black and Brown characters in ways that better reflect the racial and cultural heterogeneity of France and the world. And yet, unorthodox casting choices and visual framing distance these same characters of color from responsibility for violence. Such an approach might be interpreted as a challenge to film makers’ historical tendency to cast Black and Brown men as especially violent. However, Audiard’s films commonly elicit sympathy for white men who exercise violence. Accordingly, Audiard’s denial of authority for violence to Black and Brown characters intimates than they can only be sympathetic if seen to be more upright than his white protagonists.